Safety and Blood-Flow Outcomes for Hybrid Recanalization in Symptomatic Refractory Long-Segmental Vertebral Artery Occlusion—Results of a Pilot Study - Ma, Yan; Yang, Bin; Lu, Xia; Gao, Peng; Jiao, Liqun; Ling, Feng (Frontiers in Neurology, 2020)
Objective Hybrid recanalization for vertebral artery (VA) long-segmental occlusion using a combination of ostial vertebral endarterectomy and distal endovascular stenting has achieved technical success. The safety and efficacy of the hybrid technique should be further evaluated. Methods We examined a cohort for refractory patients with long-segmental occlusion in VA and low flow in basilar artery (BA). Hybrid technique was performed to obtain the recanalization of VA. Angiograms were analyzed for occlusive length, contralateral VA status and collaterals. Clinical variables including 30-day outcomes and blood flow changes within 6 months based on quantitative magnetic resonance angiography (qMRA) with noninvasive optimal vessel analysis (NOVA) were collected pre- and post-operatively. Results Among 290 consecutive cases with VA initial segment stenosis or occlusion, 14 patients (13 male and 1 female) with symptomatic long-segmental VA occlusion and low flow in BA were refractory to best medical therapy. Hybrid technique was successful in obtaining recanalization in all but one patient. The mean follow-up period was 17.2±9.2 months. One patient had new ischemic deficits within 7 days postoperatively. Four patients suffered from transient Horner syndrome postoperatively but recovered completely by 6-month follow-up. Within this period, all revascularization was patent by computed tomography angiography (CTA) and the blood flow in BA improved significantly (66.4±15.3ml/min vs 104.0±12.9ml/min, P < 0.05) within 6 months. No ischemic events recurred during follow-up. Conclusions Hybrid technique is a potentially safe and feasible method to achieve recanalization and improve hemodynamic compromise for long-segmental VA occlusion.